Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile - Mondaca, José; Fierro, Andrés; Rothmann, Sergio (Zootaxa, 2019)
The presence in Chile of scarab beetles (Coleoptera: Scarabaeoidea) described originally from Peru and Argentina have been reported previously, as a result of the distributional corridors through passes in the Andes Mountains (Gutiérrez 1947, 1950; Roig-Juñent et al. 2005; Ruiz-Manzanos 2006; Mondaca 2011). The purpose of this paper is to report the presence of Parochodaeus bituberculatus (Erichson, 1847) (Coleoptera: Ochodaeidae: Ochodaeinae: Ochodaeini) and Faargia gentilii (Martínez, 1975) (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini) in Chile, expanding the distribution of the second species to the west of the Andes Mountain range. The presence of both species in Chile is not surprising, due to the similarity of habitats in the collection areas with neighboring localities in Peru and Argentina.